(untitled) (International Journal of Innovative Research in Engineering & Management, 2021)
Aerodynamics is dominated by the outer design of the vehicle and extra internal components, such as the deflector connected. It is widely known that in the Indian Subcontinent a large number of light trucks without any aerodynamic characteristics are produced and operated. The main purpose of this study is therefore to assess the effect of aerodynamic devices or railways on light-duty vehicles in Pakistan and Bangladesh. The research consisted of computer modelling, production of quick physical models and wind tunnel testing, as well as CFD analysis. Nevertheless, there are a dangerous number of light trucks in the Indian sub-continent, mostly in India, Bangladesh and Pakistan that operate by changing an arrangement truck for Bedford J. The drag forces of each model were examined and matched. The results indicate that aerodynamically competent deflectors may increase the aerodynamic drag by up to 22% for most locally produced Pakistani and Bangladeshi vehicles. The aerodynamic fitting may reduce fuel consumption by 12% by altering the deflectors.